Port of Bitung Development in North Sulawesi and Its Impacts on Loading and Unloading Commodities, 1954-2005 - Hisna Hisna; Endang Susilowati; Agustinus Supriyono (Diponegoro University, 2020)
This article aims to analyze the development of the Port of Bitung in North Sulawesi and its impacts on loading and unloading commodities in 1954-2005. In 1954, the port of Bitung was designated as an ocean port. Since then, activities at the port such as ship visits and loading and unloading commodities began to run well. The physical development of the Port of Bitung in the form of basic and supporting facilities functioned as supporting activities at the port. The main facilities of Bitung Port consisted of the port area, port ponds, shipping lanes, docks, breakwater, and roads. Meanwhile, the supporting facilities consisted of warehouses, stacking fields, port administration offices, ship guides, parking lots, electricity or generator sets, loading, and unloading equipment. The physical development of Bitung Port had an impact on increasing ship visits, loading and unloading commodities at the port. Loading and unloading commodities in Port of Bitung were in the form of plantation products and the daily needs of the people of Bitung and the surrounding area.